Advertising by design generating and designing creative ideas across media - Landa, Robin (Wiley, 2016)
"A real-world introduction to advertising design in today's industry Advertising by Design is the most comprehensive, up-to-date guide to concept generation and design for advertising. Step-by-step instructions and expert discussion guide you through the fundamentals, as you develop the deeper understanding that connects the dots and sparks your creativity. Interviews with leading creative directors provide a glimpse into the real-world idea generation process, and case studies of successful ads allow you to dissect both the process and result to discover the keys to effective advertising. This new third edition has been thoroughly updated to reflect the industry's shift from print and TV ads to fully integrated transmedia campaigns, giving you invaluable insight into a broad range of media channels. New concepts and strategies for social media, digital media, pull marketing, creative content, and more are discussed in depth to help you tell an engaging story using every tool at your disposal. Ancillary materials including PowerPoint slides, quizzes, sample exercises and projects, links to video, and other online resources bring this book right into the classroom for a complete introduction to advertising design. Students seeking a career in advertising need the ability to generate idea-driven campaigns and adapt them for use in print, mobile, television, and social media formats. This book provides the well-rounded instruction required to succeed in the digital age. Master the fundamentals of advertising design for a range of media channels Integrate print, web, social media, and more to convey an engaging story Jumpstart your creativity with lessons from top creative directors Build your knowledge base around the reality of modern advertising Effective advertisers blend ideas, information, and entertainment in a way that reaches a range of audiences through a range of media types; this requires deep mastery of idea generation, copywriting, and graphic design. Advertising by Design helps you develop the skills and knowledge today's advertising industry demands"--